2017
DOI: 10.1016/j.jinf.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for cross-protection of the HPV-16/18 vaccine against HPV-6/11 positivity in female STI clinic visitors

Abstract: We observed no cross-protective effect of the bivalent vaccine on genital HPV-6/11 positivity and a non-significant partially protective effect on AGW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 25 publications
(30 reference statements)
1
9
0
Order By: Relevance
“…The qHPV and bivalent HPV vaccines are designed to cover oncogenic HPV types 16 and 18, which cause ~70% of cervical cancer cases worldwide [13] ; the qHPV vaccine also covers HPV types 6 and 11, which are responsible for 90% of genital warts cases [14] . Although partial and inconsistent cross-protection against other phylogenetically related oncogenic HPV types has been observed for both vaccines in some clinical studies, its extent, duration, and public health significance remain uncertain [7] , [11] , [15] , [16] , [17] , [18] . Population-level assessment in real-world public health programs where high coverage has occurred showed varied levels of cross-protection [16] , [17] , [18] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The qHPV and bivalent HPV vaccines are designed to cover oncogenic HPV types 16 and 18, which cause ~70% of cervical cancer cases worldwide [13] ; the qHPV vaccine also covers HPV types 6 and 11, which are responsible for 90% of genital warts cases [14] . Although partial and inconsistent cross-protection against other phylogenetically related oncogenic HPV types has been observed for both vaccines in some clinical studies, its extent, duration, and public health significance remain uncertain [7] , [11] , [15] , [16] , [17] , [18] . Population-level assessment in real-world public health programs where high coverage has occurred showed varied levels of cross-protection [16] , [17] , [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Although partial and inconsistent cross-protection against other phylogenetically related oncogenic HPV types has been observed for both vaccines in some clinical studies, its extent, duration, and public health significance remain uncertain [7] , [11] , [15] , [16] , [17] , [18] . Population-level assessment in real-world public health programs where high coverage has occurred showed varied levels of cross-protection [16] , [17] , [18] . A 9-valent HPV (9vHPV; types 6/11/16/18/31/33/45/52/58) vaccine (Gardasil 9, Merck & Co., Inc., Kenilworth, NJ, USA) was developed to provide protection against the oncogenic HPV types already covered by the existing HPV vaccines (16 and 18) and extend coverage to the 5 next most common HPV types associated with cervical cancer worldwide, including Latin America (31/33/45/52/58) [13] , [19] .…”
Section: Introductionmentioning
confidence: 99%
“…Observational studies after the implementation of large-scale immunization programs are important to assess the vaccine effectiveness (VE) against both the vaccine and nonvaccine types in the population at large. Direct effectiveness measures of the bivalent vaccine from observational studies are becoming available in the Netherlands [ 11 , 12 ], as well as other countries [ 13–16 ]. These studies showed high VE from a 3-dose schedule against the vaccine types, ranging between 73% and 100% [ 12–15 ].…”
mentioning
confidence: 99%
“…92 Some studies have shown cross-protection with the bivalent vaccine against low-risk serotypes with changes in incidence of condylomata acuminata although other studies have shown no impact. [93][94][95][96] Durability of seropositivity following HPV vaccination is yet to be established.…”
Section: Immunological Response To Hpv Vaccinationmentioning
confidence: 99%
“…Studies have also demonstrated cross‐protection to serotypes not included in the bivalent and quadrivalent vaccines associated to the development of cross‐reactive T‐cells and detectable serologic levels of specific antibodies to other low and high risk HPV types, as well as decreased detection of HPV prevalence in HPV types 31, 33, and 45 not included in the bivalent and quadrivalent vaccines . Some studies have shown cross‐protection with the bivalent vaccine against low‐risk serotypes with changes in incidence of condylomata acuminata although other studies have shown no impact . Durability of seropositivity following HPV vaccination is yet to be established.…”
Section: Introductionmentioning
confidence: 99%